Consideration and suggestion of talents team construction for information and communication industry - Li YAN; Fenfen LIN (Dianxin kexue)
Due to the rapid development of information and communication industry, there is a shortage in professional and technical personnel supplication, especially the talents. Based on the characteristics and demand of talents in information and communication industry,?discussion on how subject such as government, colleges and universities, was made. Consideration and suggestion from policy, basic education and environment creating were put forward and reference for talents team construction for information and communications industry was made.